A formação docente no projeto Cribiás, Crianças Sabidas segundo as profissionais da educação infantil de Cuiabá-MT : um estudo em representações sociais - Costa, Angela Cristina Lisboa (2020)
This research was developed in the Post-Graduation Program in Education of the Federal University of Mato Grosso, Cuiabá’s campus, in the research Line Culture, Memory and Theories of Education. It aimed to analyze the Social Representation of the Formative Process in the early Child Education in the context of the sub project Child Education as a Narrative space: Cribiás, wise children, inserted in the Extension Project: Childhood Support network: interfaces between Psychology and Pedagogy, within the Childhood Psychology Research Group. The study is characterized by being a study in the psycho-social perspective that the theoretical support is constituted in the dialogue between the Theory of Social Representations (MOSCOVICI, 2010; MARKOVÁ, 2017, JODELET, 2001, JOVCHELOVITCH, 2008), the concept of Identity Process and the Teaching Professional Development and Ongoing Formation (NÓVOA, 1995a, 1995b; MONTEIRO, 2003, IMBERNÓN, 2011). The adopted methodology was characterized by a qualitative approach developed with a group of 32 professionals of the Cuiabá Child Education System that were participating of the Ongoing Formation in question. The data production was orientated by Participative Observation (LÜDKE; ANDRÉ, 1986) and by Semistructured Individual Interviews (GASKELL, 2008; AGUIAR; OZAELLA, 2013). The data analyzes was inspired by the Studies of the Signification Core (AGUIAR; OZELLA, 2013). The results of this study has shown that the Ongoing Formative Process, analyzed by Moscovici’s approach, actuated as a forum in which the grup communication and belonging process made the familiar looks like unfamiliar generating tension between concurrent significations. The Ongoing Formative Process Cribiás, Crianças Sabidas was objectified in the images of the Flight to liberty, to new paths and new horizons. During the Ongoing Formation Process contends associated with a presctive or linear pedagogic approach the children behavior currently by adult-centered and also the professional identity of the Teacher inspired by control was put in check. The thoughts about the importance of the Narratives and the Autoral Process in the Pedagogy Participation Approach impacted on the Representation field taking account that: 1. The sharing of new contends associated with favorable attitudes to the Childhood Culture; 2. The justifying arguments of new practices in the Narrative Syllabus; 3. The knowledge circulation based in the Child Psycology and Sociology; 4. The orientation of the pedagogic practices were turned to the Autoral Narratives of the adults and the children; 5. Professional Identity Process of the teachers inspired by the notion of Atypical Adult. The Formative Process enabled new representative contend abou the pedagogic practice in the Child Education to arise based in the idea of a Dialogical Pedagogic Practice that authorize the adults and children to imagine, to create, to be, to do and to learn with the other. This practice that is actualized by the teacher’s profession experience from a sense that is based in the Childhood perspective.